Odpowiedzi

Najlepsza Odpowiedź!
2009-10-14T14:53:24+02:00
A) ((-2)^3 : ( -2 )^2 * (-2)^8)^3 / (( -2)^2 * (-2)^6 )^3 =

=((-2)^1 * (-2)^8)^3 / (( -2)^8 )^3 =
=((-2)^9)^3 / ( -2)^24=
=(-2)^27/ ( -2)^24=(-2)^3=-8

w tym przykładzie ma wyjśĆ wynik -8 .

b) 2^3 * 2^-1 + 5^-3 * 5^4 / 10^-3 : 10^-2 - (0,25)^0 =
=2²+5/10⁻¹-1=
=9/(-9/10)=-10
w tym przykładzie ma wyjśĆ wynik -10 .
2009-10-14T14:58:53+02:00
A) ((-2)^3 : ( -2 )^2 * (-2)^8)^3 / (( -2)^2 * (-2)^6 )^3 =
((-2)³:(-2)²*(-2)⁸)³ / ((-2)²*(-2)⁶)³ =
((-2)¹*(-2)⁸)³ / ((-2)⁸)³ = (-2)²⁷/(-2)²⁴=(-2)³=-8


b) 2^3 * 2^-1 + 5^-3 * 5^4 / 10^-3 : 10^-2 - (0,25)^0 =
2³*2⁻¹*5⁻³*5⁴ / 10⁻³:10⁻²-1 =
(2²+5)/10⁻¹-1 =
(4+5)/(0,1-1) =
9/-0,9 =
-10
2009-10-14T14:59:36+02:00
A) (-8:4*256)^3 / (4*64)^3 = (-512)^3 / 256^3 = (- 512/256)^3 = (-2)^3 = -8

b) (8* 1/2 + 1/125*625) / ( 1/1000 : 1/100 -1) = (4+5) / (1/1000 * 100 - 1) = 9 / (1/10 - 1) = 9 / (-9/10) = 9 * (-10/9) = -10